Down Syndrome as Pure Simulacrum. Issue 3 (1st August 2021) - Smith, Sharon; Smith, Kieron
Abstract : The article questions both the dominant metanarrative around Down syndrome and its numerous tropes, but also the dominant counter-narrative for effectively re-enforcing this. In order to expose the dominance of the image over the reality of Down syndrome, the article utilizes Baudrillard's concept of the simulacra. It demonstrates how attempts to challenge the deficit model relating to Down syndrome continue to incorporate both the specific language and underlying metaphors of Down syndrome as other. Despite greater positive visibility in advertisements, television, and the press, there continues to be an increase in terminations and no progress on inclusion in education or the workplace. The article opposes both received narratives and metaphors around Down syndrome and poses a new challenge to the disparate, but ultimately impotent dominant counter-arguments and argues for a renewed focus on the real, the material experiences of people with Down syndrome. This is the only way that the dominant prevalent image of Down syndrome can be overcome.